Long‐term consequences in critically ill COVID‐19 patients: A prospective cohort study. Issue 9 (25th June 2021) - Schandl, Anna; Hedman, Anders; Lyngå, Patrik; Fathi Tachinabad, Sozan; Svefors, Jessica; Roël, Mari; Geborek, Anne; Andersson Franko, Mikael; Söderberg, Mårten; Joelsson‐Alm, Eva; Darlington, Pernilla
Abstract : Background: COVID‐19 can cause severe disease with need of treatment in the intensive care unit (ICU) for several weeks. Increased knowledge is needed about the long‐term consequences. Methods: This is a single‐center prospective follow‐up study of COVID‐19 patients admitted to the ICU for respiratory organ support between March and July 2020. Patients with invasive ventilation were compared with those with high‐flow nasal oxygen (HFNO) or non‐invasive ventilation (NIV) regarding functional outcome and health‐related qualify of life. The mean follow‐up time was 5 months after ICU discharge and included clinical history, three well‐validated questionnaires about health‐related quality of life and psychological health, pulmonary function test, 6‐minute walk test (6MWT) and work ability. Data were analyzed with multivariable general linear and logistic regression models with 95% confidence intervals. Results: Among 248 ICU patients, 200 patients survived. Of these, 113 patients came for follow‐up. Seventy patients (62%) had received invasive ventilation. Most patients reported impaired health‐related quality of life. Approximately one‐third suffered from post‐traumatic stress, anxiety and depression. Twenty‐six percent had reduced total lung capacity, 34% had reduced 6MWT and 50% worked fulltime. The outcomes were similar regardless of ventilatory support, but invasive ventilation was associated with more bodily pain (MSD −19, 95% CI: −32 to −5) and <80% total lung capacity (OR 4.1, 95% CI: 1.3‐16.5). Conclusion: Among survivors of COVID‐19 who required respiratory organ support, outcomes 5 months after discharge from ICU were largely similar among those requiring invasive compared to non‐invasive ventilation.